SISTEM PENAKARAN AIR UNTUK PROSES PEMBUATAN ADONAN ROTI - Aidi Finawan (Jurnal Teknologi, 2014)
Scale of water for industrial bread dough on a household scale is still done manually, measured with a graduated container. Failures bread making process are  often caused by  inappropriate dosage of  water needs  due to the negligence of the workers.. Therefore, it is necessary  to figure out how to control the dosing of water easily to the dough that is   accordance to  the composition of flour needed. This research  showed  a water dosing system for dough bread flour depending on the needs of the composition. A graduated system of  the water can be applied to the  bread maker mixer and can be used for both  at home scale  or bakery industry. The mean error in testing showed frm 0,0040% to 0,0059% choice for bread and sweet bread choice. Both of these values showed  low percentage of mistakes,and it can be concluded  that a graduated system can be applied to a graduated water in the process of making bread dough